2014
DOI: 10.1080/01904167.2013.867988
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of White yam (Dioscorea rotundata) genotypes for arbuscular mycorrhizal colonization, leaf nutrient concentrations and tuber yield under NPK fertilizer application

Abstract: 2 Yield decline in yam may not only be due to soil nutrient depletion but also to the activity of soil microflora. Arbuscular mycorrhizal (AM) symbiosis helps in plant nutrition but may be affected by the application of fertilizer. The effects of nitrogen (N), phosphorus (P), and potassium (K) fertilizer rates on the AM colonization, leaf nutrient concentrations, and tuber yields of eleven genotypes of Dioscorea rotundata were investigated at Ibadan, Nigeria. The soil was ferric luvisol. Eleven genotypes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Notably, the higher nutritional requirement of yams is associated with the macronutrient's nitrogen, phosphorus, and potassium [16], confirming Dare et al's (2014) [17] report that the equivalent intake of 90 kg of N, 40 kg of P, and 74 kg of K ha −1 increased tuber production. On the other hand, research has already shown the essentiality of applying micronutrients to tubers [18,19].…”
Section: Introductionmentioning
confidence: 63%
“…Notably, the higher nutritional requirement of yams is associated with the macronutrient's nitrogen, phosphorus, and potassium [16], confirming Dare et al's (2014) [17] report that the equivalent intake of 90 kg of N, 40 kg of P, and 74 kg of K ha −1 increased tuber production. On the other hand, research has already shown the essentiality of applying micronutrients to tubers [18,19].…”
Section: Introductionmentioning
confidence: 63%
“…Diby et al (2009) and Carsky et al (2010) discussed differences in the reports on the beneficial impact of fertilizer application on yam growth and yield could be attributed to the nutrient status of the cultivation area. Dare et al, (2010Dare et al, ( , 2013Dare et al, ( , 2014 reported the potential influence of arbuscular mycorrhizal fungi that occur naturally in the yam growing areas in some of the observed variability.…”
Section: Discussionmentioning
confidence: 99%
“…Rezaei et al ( 2017 ) recently suggested that the ability of D. esculenta to grow under low N conditions would be related to the presence of N-fixing endophytic bacteria able to sustain the N nutrition of the plant. Mycorrhizal fungi can colonize yam roots, and management affects mycorrhizal communities in yam-based systems (Tchabi et al, 2008 , 2009 ; Dare et al, 2013 , 2014 ). However, we still lack knowledge on the impact of mycorrhizae in the field and on how to manage them to improve yam yield.…”
Section: Importance Of Soil Fertility For Yam Productionmentioning
confidence: 99%